Sociocultural factors of vocational education upgrade - Golubovski, Valeri N. (University Pedagogical Journal, 2023)
The nature of sociocultural activities, its structure and content are reviewed. The results of sociocultural activities and their influence on the factors predetermining the upgrade of vocational education system are studied. The place and role of education in the sociocultural activities of a person, its influence on the life of society and the development of human capital are determined.
Keywords: vocational education; sociocultural factors; sociocultural activity; upgrade; content of education